THE TOURISM FUNCTION DETERMINANTS OF THE RURAL MUNICIPALITIES IN PODKARPACKIE PROVINCE, POLAND - Górecka, Aleksandra (Acta Scientiarum Polonorum. Oeconomia, 2011)
The tourism potential is defined as the elements like the natural environment (natural) and cultural (anthropogenic) amenities, which form the basis for tourism development. Properly managed and exposed become prominent, often unique tourist values, that are already real tourist attractions encouraging visitors to arrive at that area. Tourism potential is perceived as a major aspect in the formation of a region’s tourism function. This article aims at identifying the tourism potential element, of seven, which is the most essential for the shaping of the said function. The research for this paper was conducted in 2006–2007, covering all the rural and combined urban-rural municipalities in Podkarpackie province, Poland.